Surface modification of liquid metal as an effective approach for deformable electronics and energy devices - Bark, Hyunwoo (2021)
The fields of flexible or stretchable electronics and energy devices, reconfigurable and compliant soft robotics, wearable e-textiles or health-care devices have paid significant attention to the need of deformable conductive electrodes due to its critical role in device performances. Gallium-based liquid metals, such as the eutectic gallium-indium (EGaIn) being an electrically conductive liquid phase at room temperature, have attracted immense interests as a promising candidate for deformable conductor. However, in the case of bulk liquid metal, there are several limitations such as the need of encapsulation, dispersion in a polymer matrix, or accurate patterning. For these reasons, the preparation of liquid metal particles in harnessing the properties in a non-bulk form and surface modification is crucial for the success of incorporating liquid metal into functional devices. Herein, we discuss the current progress in chemical surface modification and interfacial manipulations of liquid metal particles. The physical and chemical properties of the surface modification-assisted liquid metal polymer composite are also reviewed. Lastly, the applications of the surface-modified liquid metal particles such as flexible electrode, soft robotics, energy storage or harvester, thermal conductor, dielectric sensor, and bioelectronics are discussed, and the corresponding perspectives of deformable electronics and energy devices are provided. In particular, we focus on the functionalization method or requirement of liquid metal particles in each application. The challenging issues and outlook on the applications of surface-modified liquid metal particles are also discussed.